Mechanical performance of carbon - aramid fiber-reinforced laminated composites under impact and shear loading - EKİCİ, BÜLENT (My University, 2021)
In this study, the drop weight impact response and the interlaminar shear strength of hybrid carbon/aramid fiber-reinforced laminated composites with different stacking sequences were investigated. Seven different laminates including two types of sandwich-like interply hybrid, three types of interply hybrid, and two types of non-hybrid named carbon and aramid were produced using the vacuum-assisted resin transfer molding method. Drop weight impact and short-beam shear tests were applied to the laminates to calculate the low-velocity impact response and the interlaminar shear strength, respectively. It is observed that while the outer layer of the hybrid structure is carbon, the structure can carry less load but absorb more energy. Pure carbon and pure aramid composites cannot carry loads but can absorb energy as much as their hybrid versions can. Sandwich-like interply hybrid with central carbon showed the best results when load and energy values were compared. Also, sandwich-like interply hybrid with central carbon has higher ILSS among hybrid structures because its center region consists of carbon layers.
Keywords: Carbon fiber; Aramid fiber; Hybrid composites; Low-velocity impact response; Interlaminar shear strength (ILSS)